Effects of post-training heroin and d-amphetamine on consolidation of win-stay learning and fear conditioning. (March 2013) - Leri, Francesco; Nahas, Elia; Henderson, Katherine; Limebeer, Cheryl L; Parker, Linda A; White, Norman M
It has been proposed that the reinforcing properties of drugs of abuse are due, in part, to their ability to enhance memory consolidation. To test this hypothesis, heroin (0.03–3 mg/kg, SC) and d-amphetamine (0.5–2 mg/kg, SC) were administered to male Sprague-Dawley rats immediately or 4 h after training on win-stay and fear conditioning tasks. On the win-stay, immediate post-training administration of lower doses of heroin and d-amphetamine enhanced acquisition, and probe tests further revealed that these drugs enhanced different aspects of learning. Higher doses had no effect or impaired performance, particularly when administered repeatedly. On fear conditioning, the memory-enhancing effects of immediate post-training administration of lower heroin and d-amphetamine doses were revealed only when a single tone–shock pairing procedure was employed. Therefore, under appropriate experimental conditions, mildly stimulatory doses of heroin and d-amphetamine enhanced the acquisition of tasks thought to involve different types of learning. These results support the hypothesis that one of the ways in which drugs of abuse such as opiates and psychomotor stimulants reinforce behavior is by enhancing memory consolidation processes.